Human Responses to the Divine: Eric Voegelin's Philosophy of Consciousness and Symbolization - Srigley, Ronald D. (My University, 1990)
The history of western philosophy has been characterized by an ongoing discussion about the relation between theology and philosophy. This thesis is an attempt to understand the nature of this relation through an analysis of Eric Voegelin's philosophy of consciousness and symbolization. We attempt to show how Voegelin's philosophical analysis of consciousness affords us insight into the nature of both true and false theology. Our argument is based on Voegelin's discussion of the conception of theology developed by Plato in Book II of the Republic. According to Plato, the term theology is descriptive both of the symbolism of divine reality employed by consciousness, and the state of consciousness that that symbolism expresses. We argue, therefore, that an understanding of the various human responses to divine reality cannot be separated from an understanding of the true nature of consciousness and its deformation.
In the first chapter of this study we outline Voegelin's understanding of the true nature of consciousness and its symbolic expression. In Chapter II we critically assess several deformative understandings of consciousness by placing them alongside Voegelin's analysis. Our study concludes with a discussion of two questions that arise in response to the analysis of Chapters I and II: (1) How is one to move from a state of deformation to a true state of existence? (2) How is this true state established as true?
Keywords: Religious Studies; Religion; Religion